Studi Eksistensi Dynamic Trade-Off Capital Structure Pada Perusahaan Non-Finansial Di BEI Periode 2002-2009 - Leo Atansil (Universitas Airlangga, 2012)
This research aims to analyze the factors which affect capital structure and also discover the existence of dynamic trade-off capital structure. Variables which use are profitability, tangibility, size, growth, non-debt tax shields, and operating risk. This research use quantitative approach by using multiple linier regression. This research use samples in the form of non-financial company which are listed in Indonesian Stock Exchange on 2002-2009. Final samples which are utilized in this research are equal to 375 observation. Research finding indicates that profitability, tangibility, and size doesn’t affect significantly to capital structure. Growth, non-debt tax shields, and operating risk give significantly negative effect to capital structure. This research also finds that the company doing adjustment exceeds the level required to achieve the optimum debt (over-adjustment) so that the company’s capital structure are not optimum.